2004
DOI: 10.1002/jcb.20272
|View full text |Cite
|
Sign up to set email alerts
|

Paradigmatic identification of MMP‐2 and MT1‐MMP activation systems in cardiac fibroblasts cultured as a monolayer

Abstract: Activations of MMP-2 and membrane type 1-matrix metalloproteinase (MT1-MMP) have been correlated with cell migration, a key cellular event in the wound healing and tissue remodeling. We have previously demonstrated furin-dependent MMP-2 and MT1-MMP activations induced by type I collagen in cardiac fibroblasts. To understand mechanistic aspects of the regulation of MMP-2 and MT1-MMP activations by potential non-matrix factor(s) in cardiac fibroblasts, in the present study, we examined the effects of various age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Our data also demonstrate that Rho/ROCK signaling and subsequent cytoskeletal rearrangement mediated increased localization of MT1-MMP to the plasma membrane in response to leptin, which may have several important functional consequences (9,26,38,39). First, based on our previous work in cardiac fibroblasts (9), we further investigated whether leptin-induced increased cell surface localization of MT1-MMP regulated activation of secreted pro-MMP-2.…”
Section: Discussionmentioning
confidence: 83%
“…Our data also demonstrate that Rho/ROCK signaling and subsequent cytoskeletal rearrangement mediated increased localization of MT1-MMP to the plasma membrane in response to leptin, which may have several important functional consequences (9,26,38,39). First, based on our previous work in cardiac fibroblasts (9), we further investigated whether leptin-induced increased cell surface localization of MT1-MMP regulated activation of secreted pro-MMP-2.…”
Section: Discussionmentioning
confidence: 83%
“…We found that although arginine substitutions at the Gly 284 -Gly 285 site inhibited formation of the 44-kDa species, they did not prevent processing. Instead, the MT1-MMP mutants underwent alternate cleavages at downstream sites, within the hinge region, to generate smaller degradation products (ϳ41-kDa), similar to those detected under conditions of enzyme overexpression (31, 36 -38) or inhibition of endocytosis (39). The pattern of processing exhibited by a series of MT1-MMP C-terminal hinge deletion mutants, which preserve the Gly 284 -Gly 285 site, points to the region located between Gln 296 and Ser 304 of the hinge region as the main target for the additional cleavage site(s) during processing.…”
Section: Processing Of Mt1-mmp As a Function Of Time And Level Of Expmentioning
confidence: 84%
“…The processing of MT1-MMP is a cell surface event in which the active enzyme is autocatalytically cleaved in trans to a major 44-kDa membrane-tethered degradation form (also referred to as the 43-or 45-kDa species) lacking the catalytic domain. A series of minor degradation products of 43-40 kDa can also be detected under conditions of enzyme overexpression (31, 36 -38) or exposure of cells to concanavalin A, which inhibits MT1-MMP endocytosis (39). Concomitantly, a fragment of the catalytic domain is released into the extracellular space as an inactive 18 -20-kDa soluble form (30,33).…”
Section: Matrix Metalloproteinases (Mmp(s))mentioning
confidence: 99%
See 1 more Smart Citation
“…This concept has been supported by Sato et al, who demonstrated that recombinant MT1‐MMP was efficiently cleaved in vitro by purified soluble furin [27], [42,45,46]. Interestingly, furin inhibition either with a synthetic inhibitor (decanoyl‐Arg‐Val‐Lys‐Arg‐chloromethylketone, or CMK) or antisense technology resulted in a reduced Pro‐MT1‐MMP and MMP‐2 activitation in cardiac and uterine cervical fibroblasts [47,48] but not in rabbit dermal fibroblasts [48]. These results suggest that furin involvement in MT1‐MMP maturation and consequently in the regulation of collagenolytic modulation may be species‐, tissue‐, and/or cell type‐dependent.…”
Section: Introductionmentioning
confidence: 97%